Dynamic Characteristics Analysis and Enhancement for Superconducting EDS Trains at Curved Track - Feng, Piji; Ma, Guangtong; Su, Zhenhua; Cui, Libin; Zhu, Taoning; Luo, Jun; Song, Mingyan (IEEE transactions on transportation electrification, 2025)
The studies of superconducting electrodynamic suspension (EDS) have gradually received more and more attention in recent years. As the inevitable line condition, the horizontal curved track would change the relative spatial position between the onboard superconducting magnet (SCM) and ground levitation/guidance (LG) coils, resulting in the different vehicle-track coupled forces compared to straight track conditions, which prominently influences the dynamic performance of EDS trains. This paper proposed an analytical calculation method of vehicle-track force that can describe arbitrary curved track parameters. Based on this calculation method, the dynamic model of EDS trains considering the curved track conditions was built. Meanwhile, an equivalent loading method for track irregularities was proposed, which is applicable to both real electromagnetic force case and fitting force case in dynamic scenarios. The calculation results indicate that under curved track conditions, the lateral and rolling dynamic characteristics of vehicles deteriorates significantly and the effect of the higher harmonics of electromagnetic forces is enhanced. In order to suppress the violent vibration of SCMs, a ground-hook semi-active strategy at the primary suspension was adopted and the results indicate that it can effectively improve the lateral displacements and accelerations of SCM units, but the suppressing effect of high-frequency vibrations is moderate. This research provides valuable references to clarify the dynamic characteristics of EDS trains at curved track and a new approach to suppress vibrations of SCMs.